Comparative study of torque expression and its biomechanical effects: spherical self-ligating bracket with lock-hook system versus passive self-ligating bracket and conventional bracket - Yudong Liu; Longmei Guo; Yanqing Feng; Jiahao Hua; Qingyuan Dai; Ziyang Chen; Wenlu Song; Bing Guo; Taicong Chen; Li Ji (BMC Oral Health)
Abstract Background Proper torque control is crucial to the outcome of orthodontic treatment. This study aimed to employ finite element analysis to compare the torque capabilities of a novel spherical self-ligating bracket with a lock-hook system against those of commonly used passive self-ligating and conventional bracket systems, as well as to reveal the biomechanical changes in the periodontal ligament (PDL) during torque expression. Methods A maxillary right central incisor, along with its PDL and alveolar bone, were modeled. Three types of brackets were selected: a spherical self-ligating bracket with a lock-hook system, a passive self-ligating bracket (Damon), and a conventional bracket (Discovery). Each bracket was equipped with a 0.022-inch slot and a 0.019 × 0.025-inch stainless steel archwire. A palatal root torque of 20° was applied. The torque moment, as well as the von Mises stress and strain in the PDL, were calculated. A clinical case involving the lingual inclination of the upper anterior teeth was utilized to assess the feasibility of using the spherical self-ligating bracket with the lock-hook system to express torque. Results At a twist angle of 20°, the maximum torque generated by the spherical self-ligating bracket with a lock-hook system (27.8 N·mm) was approximately 1.6 times greater than that of the Damon bracket (17.5 N·mm) and the Discovery bracket (17.3 N·mm). As the twist angle increased, both the von Mises stress and the strain in the PDL also increased. When the maximum PDL stress was less than 0.026 MPa and the percentage of the PDL good strain area (defined as the area with PDL strain ≥ 0.3%) exceeded 50%, the torque range for the maxillary incisor was between 10.2 and 17.5 N·mm. The clinical case demonstrated that the use of the spherical self-ligating bracket with the lock-hook system effectively corrected the unfavorable linguoclination of the maxillary incisors. Conclusions The spherical self-ligating bracket with a lock-hook system can significantly enhance torque expression. The optimal torque range for the maxillary incisor is between 10.2 and 17.5 N·mm.